3D MAGNETIC MODEL OF THE EARTH CRUST OF THE EASTERN EUROPEAN CRATON WITH THE ACCOUNT OF THE EARTH SPHERICITY AND ITS TECTONIC INTERPRETATION - Orlyuk, M.; Marchenko, A.; Bakarjieva, M. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The geomagnetic field is widely used to obtain information on the deep structure and development of the Earth’s lithosphere, small-scale forecasting of minerals, and the solution of a number of environmental problems. The most significant results are obtained due to the development of 2D, 3D and 4D magnetic models of the Earth’s crust (lithosphere) in which the spatial and spatiotemporal distribution of magnetic sources is reflected. The reliability of the spatiotemporal distribution (location) of magnetic sources and the magnitudes of their magnetization depends on the adequacy of taking into account the geometry of objects and the inhomogeneity of the Earth’s main magnetic field. In this regard, for the East European Craton for the first time its regional 3D magnetic model for a spherical Earth is developed. To develop the model, we used digital data WDMAM at a height of 5 km, a priori data on the depths of the surface of the crystalline basement and Moho, the temperature distribution, as well as the results of other geological and geophysics researches. According to S.V. Bogdanova, the Eastern European Craton was formed due to the suturation of three segments (Fennoscandia, Volgo-Uralia and Sarmatia) in a time interval of 2,1–1,8 Ga. At the Phanerozoic stage of development, the modern borders of the craton were formed. It is established that a non-uniform distribution of magnetic sources and magnitudes of their magnetization is observed on the boundaries of the craton. The maximum concentration of magnetic sources is characteristic for the edge parts of the craton. The southwestern boundary of the craton is marked by magnetic sources with a magnetization of (1,0–3,0) A/m at depths of (10–18÷46) km. Stretching of the sources is consistent with the stretch of the Trans-European sutural zone and the Baltic-Transnistrian zone of pericratonic troughs (subsidence). The stretching of magnetic sources in the southeast of the craton within Fennoscandia and the Volgo-Uralia is coordinated with the strike of the Phanerozoic structures of the Ural and Timan. Magnetic sources lie in the interval (10–18÷38–44) km and have a magnetization of (0,7–4,0) A / m. Magnetic sources of the northern (within Fennoscandia) and southern (within Sarmatia) parts of the craton have an end joint with its boundary. The zones of articulation of the EEC segments are also distinguished by sources of regional magnetic anomalies. Magnetic sources of the Central-Russian rift system divide the magnetic crust of the Volgo-Uralia and the weak magnetic crust of Fennoscandia, and the sources of the Volyn-Orsha rift system are Fennoscandia and Sarmatia. Magnetic sources of the Pachelma rift zone are separated by Sarmatia and Volgo-Uralia. We note that approximately the same strike has magnetic anomalies of the Kursk-Bryansk band with maximal values of the magnetization of their sources within the limits of the craton (˃10,0 A/m). According to the concept of tectonics of lithospheric plates, the magnetic inhomogeneity of the zones of suturation of the segments of the craton and its outer boundaries can be considered as sources of subduction type, which arose at the stage of their formation. In the Riphean and Phanerozoic stages of the development of the lithosphere within the zones of suturation of the segments of the craton and its outer boundaries, magnetic sources of rift nature were formed. Magnetic sources of subduction-reduction and rifting types are characterized by a corresponding metallogenic specialization, therefore the developed model can be used both for tectonic constructions and for small-scale forecasting of minerals.